Role of CT scan in the evaluation of lung tumor with cytopathilogical correlation (Faridpur Medical College Journal, 2015)
Lung cancer is an important & widespread disease that contributes a major health problem worldwide. Lung cancer kills over 1 million people per year. Cigarette smoking is the major cause of lung cancer. CT scan is the principal radiological examination adjunct to X-Ray chest examination in diagnosis & management of lung cancer. The main Objective of the study was to assess the diagnostic usefulness of CT scan in evaluating & characterize the different types of lung tumors and to correlate CT findings of lung tumors with that of cytopathology. This study was carried out in the department of Radiology & Imaging, Dhaka medical college hospital, Dhaka during the period from 1st January 2007 to March 2008. It was a cross sectional study. Total 51 patients were selected conveniently, detailed history particularly symptoms related to lung tumors was carefully elicited to obtain maximum possible information regarding the illness. Possible diagnosis was established by the combination of history, physical examination, laboratory & radiological investigations. Then patients were underwent CT examination of lung. Cytopathological sample were obtained from the lesion by guided aspiration. Collected FNAC samples were send for cytopathology & collected reports were compared with CT scan reports. Sensitivity of CT to diagnose lung tumor was 97.4%, specificity 76.9% & accuracy 92.2 %.Faridpur Med. Coll. J. 2014;9(1): 37-41